1983
DOI: 10.3354/meps012207
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of the southern sea garfish Hyporhamphus melanochir: gut passage rate and daily consumption of two food types and assimilation of seagrass components

Abstract: The southern sea garfish Hyporhamphus melanochir fed on the seagrass Heterozostera tasmanica for 13 h during daylight, ingesting an estimated 3 gut volumes of plant matter, equivalent to 500 kJ d-I kg-' dry wt. No cellulase was detected in garfish digestive tissues, and gut pH was near neutral, but the pharyngeal mill efficiently triturated the seagrass tissue. Seagrass frond was assimilated at an efficiency of 38 % (organic matter). 28 % (energy). 50 % (protein) and 76 % (lipids), these being equivalent to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
83
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 33 publications
4
83
2
Order By: Relevance
“…In particular, seagrasses often have elevated C:N ratios, due to high levels of structural carbohydrates (lignin and cellulose) that cannot be easily digested by most marine organisms (e.g. Klumpp & Nichols 1983) and might influence preference and/or ingestion rates by consumers. Other factors such as caloric content, amount of organic matter, total protein and total lipid content may also be detected by grazers and result in enhanced consumption rates of higher quality plants (Montgomery & Gerking 1980, Targett & Targett 1990.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, seagrasses often have elevated C:N ratios, due to high levels of structural carbohydrates (lignin and cellulose) that cannot be easily digested by most marine organisms (e.g. Klumpp & Nichols 1983) and might influence preference and/or ingestion rates by consumers. Other factors such as caloric content, amount of organic matter, total protein and total lipid content may also be detected by grazers and result in enhanced consumption rates of higher quality plants (Montgomery & Gerking 1980, Targett & Targett 1990.…”
Section: Introductionmentioning
confidence: 99%
“…They are particularly abundant in coastal waters, some species penetrate estuaries into freshwater, and a fe w complete their life-cycle in freshwater (Collette et al, 1984). Herbivory is widely reported for the coastal species (Talwar, 1962;Randall, 1967;Thomson, 1959;Robertson, 1978Robertson, , 1980Blaber, 1980;Blaber and Blaber, 1980) and they have been implicated in nutrient recycling (Klumpp & Nichols, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important when one considers that hemiramphids have a relatively small gut length to total body length ratio (Klumpp & Nichols, 1983), which is commonly considered to be a fe ature of carnivorous fish (Kapoor, 1972). Since it has been reported that their pharynx plays an important role in food treatment (Klumpp & Nichols, 1983) and no functional morphological examination of the structure has been forthcoming it seemed advisable to carry out this work. Certain modem analytical techniques are available and the application of these might not only throw light upon the unusual alimentary specializations of hemiramphids but, also on certain anomalies (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations